(untitled) (Global Journal of Science Frontier Research, 2012)
In this paper,nonlinear differential equations are solved through Adomian decomposition method(ADM) and the results are compared with those of Picard iterations method. It is noted that ADM takes the form of a convergent series with easily computable components. The ADM method is able to solve large class of nonlinear equations effectively, more easily and accurately; and thus the method has been widely applicable to solve any class of equations in sciences and engineering.